Competitiveness Analysis and Factors Affecting Indonesian Rubber Exports in BRICS Plus Countries - Sambhoro, Farrel Rizqi; Setiawan, Budi; Hartono, Rachman (Universitas Panji Sakti, 2025)
By leveraging its potential as a new member of BRICS, Indonesia can enhance its international trade through increased economic and trade cooperation within the group. BRICS integration can help improve Indonesia's trade balance and reduce its dependence on traditional markets, as it provides Indonesia with access to new markets and opportunities to diversify its export partners. This is the first study to analyze Indonesian rubber competitiveness and key determinants specifically across BRICS-Plus countries following official 2025 accession, providing one of the first empirical assessments in the context of Indonesia’s prospective 2025 BRICS accession. Using Revealed Comparative Advantage (RCA) and multiple linear regression methods with annual data from 2001 to 2023, the study evaluates both comparative advantage and the factors influencing export performance. The independent variables include the GDP of BRICS countries, Indonesia’s GDP, world rubber prices, exchange rate, inflation rate, population, and export restriction policy. The RCA results show that Indonesia holds a comparative advantage in most BRICS markets; however, competitiveness remains relatively weak in India and China, the two largest importers of Indonesian rubber. Regression analysis indicates that three variables significantly and positively affect Indonesia’s rubber export value, namely the GDP of BRICS nations, international rubber prices, and the rupiah exchange rate. These findings imply that macroeconomic coordination, diversification of export destinations, and stabilization of the exchange rate are crucial to enhancing Indonesia’s trade performance within BRICS. Strengthening competitiveness in key markets will be essential for Indonesia to optimize its economic gains and reinforce its position in the global rubber trade following full integration into the BRICS framework.